Mapping Strategy Development Of Traveler Destinations In Empowerment Local Community East Coast In South Sulawesi - Nur, Andi Cudai Nur; Niswati , Risma; Cante, Slamet Riadi; Mustafa, Delly; Akib, Haedar (Samarinda State Polytechnic, 2021)
Research carried out to identify, analyze, and orientation of the mapping strategy to support the development of tourism destinations empowering local communities and area-based tourism as its leading sector. The approach used is qualitative and quantitative mix techniques. The results showed that developments rating in Sinjai can be seen from 1) traveller, 2) traveller destination, 3) traveller activities, 4) of accommodation used, 5) traveller trips, 6) average expenditure, 7) characteristics of the traveller market. From the description of the results of the study has increased every year. This is because adequate infrastructure increasingly supported sights. The mapping showed an increase and expansion of the traveller area each year. Increased traveller destinations and the availability of adequate infrastructure provide the opportunity for local communities to take part in the tourism industry that contributes to the empowerment of local communities. The government's efforts in promoting the expansion of development opportunities in various sectors of the tourism sector strongly support the improvement of the economy and social life at the local community level.